Ramificación en el proceso de enseñanza - aprendizaje en la asignatura de ciencias sociales a los estudiantes de 10mo año de básica en la Unidad Educativa “Guaranda”. - García Fernández, Alexander Paul (2024)
The current research aims to address a personal conflict regarding our future careers as educators: understanding how teaching strategies are implemented and how to improve learning outcomes so that students can enhance their learning, develop their own genuine processes, and become autonomous in their development. Branching out is the ability to foster a deeper and more contextualized understanding of subjects. By exploring connections between different concepts and disciplines, students can develop critical thinking, analysis, and synthesis skills, as well as a broader appreciation of the interconnection between the social, political, economic, and cultural aspects of the world. This promotes a comprehensive education that prepares students to face real-world challenges with an informed and reflective perspective.